2011
DOI: 10.1016/j.bpj.2011.10.043
|View full text |Cite
|
Sign up to set email alerts
|

The Layered Structure of Coronary Adventitia under Mechanical Load

Abstract: The mechanical loading-deformation relation of elastin and collagen fibril bundles is fundamental to understanding the microstructural properties of tissue. Here, we use multiphoton microscopy to obtain quantitative data of elastin and collagen fiber bundles under in situ loading of coronary adventitia. Simultaneous loading-imaging experiments on unstained fresh coronary adventitia allowed morphometric measurements of collagen and elastin fibril bundles and their individual deformation. Fiber data were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
93
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 34 publications
4
93
0
Order By: Relevance
“…Our experimental studies showed that coronary adventitia is divided into outer and inner adventitia, as shown in Fig. 1 (3,6). The outer adventitia, consisting of thicker and wavier collagen bundles and few elastin fibers, supports the vessel and connects with the surrounding tissue rather than significantly resisting the transmural pressure ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our experimental studies showed that coronary adventitia is divided into outer and inner adventitia, as shown in Fig. 1 (3,6). The outer adventitia, consisting of thicker and wavier collagen bundles and few elastin fibers, supports the vessel and connects with the surrounding tissue rather than significantly resisting the transmural pressure ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The cross sections of the frozen segment were sectioned by a cryostat microtome, mounted on microscope slides, and viewed by an FV1000-MPE multiphoton microscope (MPM; Olympus America, Center Valley, PA), which is equipped with a Mai Tai DeepSee tunable laser (Spectra-Physics, Santa Clara, CA). A combination of second harmonic generation and two-photon excitation fluorescence was set up to detect signals of collagen and elastin fibers simultaneously (3,6,49). The excitation wavelength of the laser was 830 nm, and emission wavelengths for collagen (second harmonic generation) and elastin (second harmonic generation) were 415 and 520 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been observed that valvular tissues are largely strain-rate insensitive (63), so that the responses measured here are likely to represent the in vivo response. The SHG imaging systems has been successfully utilized previously in several studies (7,64,65), although it does have resolution limitations and the results presented herein are necessarily limited by the technique's ability to distinguish fiber structures. Overall, our fiber-level results are a good approximation of the ensemble fiber responses, but we cannot rule out local (i.e., submicron scale) nonaffine deformations of individual fibers.…”
Section: Study Limitationsmentioning
confidence: 99%